2022
DOI: 10.53378/352909
|View full text |Cite
|
Sign up to set email alerts
|

Pre-service Teachers’ Readiness on Online Learning and their 21st Century Pedagogical Skills

Abstract: This study looked at the online learning readiness and 21st century pedagogical skills among pre-service teachers of a state university in the Philippines during the school year 2021-2022. The descriptive-correlational method was applied through an adapted survey questionnaire administered to 28 pre-service teachers. The findings revealed that pre-service teachers were ready for online learning in terms of computer/internet self-efficacy, self-directed learning, learner control, motivation for learning, and on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 22 publications
1
2
1
Order By: Relevance
“…We failed to find a significant effect of age, marital status, or employment status on pre-service teachers' online skill development and satisfaction. Again, we identified no consistent prior findings, although other studies found online classroom management (Taghizadeh and Amirkhani, 2022), 21st-century pedagogical competencies (Malabanan et al, 2022), and interest in job choices (Shen and Chee Luen, 2022) to be relevant factors in pre-service teachers' online skill development. These findings suggest that demographic factors do not significantly impact online skill development.…”
Section: Research Questioncontrasting
confidence: 87%
See 3 more Smart Citations
“…We failed to find a significant effect of age, marital status, or employment status on pre-service teachers' online skill development and satisfaction. Again, we identified no consistent prior findings, although other studies found online classroom management (Taghizadeh and Amirkhani, 2022), 21st-century pedagogical competencies (Malabanan et al, 2022), and interest in job choices (Shen and Chee Luen, 2022) to be relevant factors in pre-service teachers' online skill development. These findings suggest that demographic factors do not significantly impact online skill development.…”
Section: Research Questioncontrasting
confidence: 87%
“…The results of the current study indicate that pre-service teachers' engagement and motivation in online education are more effective when they are unemployed. This finding of a positive relationship of engagement and motivation with employment status is consistent with some studies (Ogbonnaya et al, 2020;Malabanan et al, 2022) but inconsistent with others. For example, Gussen et al (2023) concluded that many pre-service teachers have negative attitudes toward research and lack the motivation to conduct it, while Ye et al (2021) found that pre-service teachers demonstrated better motivation than beginners, except for a few factors like intrinsic value and teaching skills.…”
Section: Research Questionsupporting
confidence: 70%
See 2 more Smart Citations